2015
DOI: 10.4049/jimmunol.1500104
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation in SP-A2 Leads to Differential Binding to Mycoplasma pneumoniae Membranes and Regulation of Host Responses

Abstract: Mycoplasma pneumoniae (Mp) is an extracellular pathogen that colonizes mucosal surfaces of the respiratory tract and is associated with asthma exacerbations. Previous reports demonstrate that surfactant protein-A (SP-A) binds live Mp and mycoplasma membranes (MMF) with high affinity. Humans express a repertoire of single amino acid genetic variants of SP-A that may be associated with lung disease, and our findings demonstrate that allelic differences in SP-A2 (Gln223Lys) affect the binding to MMF. We show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 42 publications
2
29
0
Order By: Relevance
“…Because some lipopeptides, including FSL‐1 and Pam3CSK4, have shown to induce NETs release via TLR2 (Marcos et al, ), the receptor might participate in the induction of NETs release by M. pneumoniae . In contrast, early studies have shown that M. pneumoniae induces inflammatory responses independently of TLR2 (Chmura et al, ; Shimizu et al, ; Ledford et al, ), suggesting that receptors other than TLR2 may also take a part in the NETs release from neutrophils upon M. pneumoniae infection.…”
Section: Discussionmentioning
confidence: 91%
“…Because some lipopeptides, including FSL‐1 and Pam3CSK4, have shown to induce NETs release via TLR2 (Marcos et al, ), the receptor might participate in the induction of NETs release by M. pneumoniae . In contrast, early studies have shown that M. pneumoniae induces inflammatory responses independently of TLR2 (Chmura et al, ; Shimizu et al, ; Ledford et al, ), suggesting that receptors other than TLR2 may also take a part in the NETs release from neutrophils upon M. pneumoniae infection.…”
Section: Discussionmentioning
confidence: 91%
“…According to a recent study, phosphorylation of EGFR was increased in the lungs by mycoplasma membrane fraction stimulation in SP-A knock-out mice (36). These results suggested that SP-A down-regulates EGFR activity in vivo.…”
Section: Sp-a Down-regulates Egf Signalingmentioning
confidence: 90%
“…We used a total of 10 C57BL/6 mice, 5 SP‐A (−/−) knockouts and 5 humanized transgenic (hTG) SP‐A2 knockins (+/−) . The animals were euthanized by CO 2 asphyxiation and whole nasal meatuses were harvested and snap frozen with liquid nitrogen followed by Bessman tissue pulverization.…”
Section: Methodsmentioning
confidence: 99%